2013
DOI: 10.2519/jospt.2013.4680
|View full text |Cite
|
Sign up to set email alerts
|

Baseball Players Diagnosed With Ulnar Collateral Ligament Tears Demonstrate Decreased Balance Compared to Healthy Controls

Abstract: Study Design Cross-sectional. Objectives To compare lower extremity balance and shoulder range of motion in baseball players with ulnar collateral ligament (UCL) tears to a healthy cohort. Background Throwing is a complex motion that requires balance and coordination to effectively transfer energy through the kinetic chain. In theory, poorer balance could negatively affect throwing mechanics and lead to injury. Methods Thirty baseball players (mean ± SD age, 18.5 ± 1.9 years) with a diagnosis of a UCL tear of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 23 publications
3
71
2
1
Order By: Relevance
“…Several studies have reported that dysfunction in the trunk or lower extremities has a significant association with elbow and shoulder injuries in adult overhead athletes (Scher et al 2010;Feigenbaum et al 2013;Garrison et al 2013;Chaudhari et al 2014;Pontillo et al 2014;Radwan et al 2014). Some studies have demonstrated that poor core stability should be considered as a potential risk factor for elbow and shoulder injuries (Garrison et al 2013;Chaudhari et al 2014;Pontillo et al 2014;Radwan et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that dysfunction in the trunk or lower extremities has a significant association with elbow and shoulder injuries in adult overhead athletes (Scher et al 2010;Feigenbaum et al 2013;Garrison et al 2013;Chaudhari et al 2014;Pontillo et al 2014;Radwan et al 2014). Some studies have demonstrated that poor core stability should be considered as a potential risk factor for elbow and shoulder injuries (Garrison et al 2013;Chaudhari et al 2014;Pontillo et al 2014;Radwan et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated that poor core stability should be considered as a potential risk factor for elbow and shoulder injuries (Garrison et al 2013;Chaudhari et al 2014;Pontillo et al 2014;Radwan et al 2014). Other studies have shown an association between hip range of motion, as well as foot posture, with elbow and shoulder injuries.…”
Section: Discussionmentioning
confidence: 99%
“…6,11,25 Historically, GIRD was thought to be a primary contributing factor to both shoulder and elbow injuries in overhead throwing athletes due to the concomitant hyperexternal rotation associated with the loss of internal rotation. GIRD has been attributed to tightness in the posterior glenohumeral joint capsule, myofascial restrictions, laxity of anterior glenohumeral joint capsule, and osseous changes that result in humeral retroversion.…”
Section: Shoulder Screeningmentioning
confidence: 99%
“…Literature suggests that year-round training and competition increases the likelihood of a youth baseball pitcher suffering a shoulder or elbow injury. 10,11 The number of pitches thrown, the type of pitches thrown, and the overall physical fitness of the youth baseball pitcher can increase the risk for shoulder and elbow injuries. 10,12,15 Fifteen percent of college-level pitchers consider injuries sustained playing youth baseball have limited current performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation